INVESTIGACIONES SOBRE GLOBULINAS CRISTALIZADAS DE SEMILLAS DE CALABAZA - SALAZAR, V; CASTANEDA AGULLO, M (Instituto de Salubridad y Enfermedades Tropicales, CD MEXICO, DF, MEX, 1950)
The serologic characteristics of dextran polysaccharides synthetized from sucrose by 2 Leuconostoc strains (A-6 and B-l) isolated from pulque were investigated These strains gave precipitin reactions with antisera produced by immunization with sucrose-gr
AN ESC NAC CIENC BIOL
Keywords: INVESTIGACIONES, GLOBU LINAS CRISTALIZADAS, SEMILLAS DE CALABAZA; CIENCIAS DE LA VIDA; BIOLOGIA VEGETAL; BOTANICA GENERAL